Labeling Schemes to Support Dynamic Updates on XML Trees: A Technical Review - Amin, Aisyah; Su, Cheng Haw; Subramaniam, Samini; Soong, Emyliana (2018)
eXtensible Markup Language (XML) are widely use on World Wide Web (WWW) for data exchange purpose due to its expressivity and extensible nature. With the fast growing rate of data, especially with high updates, it is important to ensure that the XML is able to cope with frequent changes with very least affect on the existing structure. To ensure the structural relationships are preserved, XML tree is commonly annotated with labeling scheme. Various labeling schemes emerged with the intention to ensure that it is persistent, robust and durable enough to sustain the re-labeling due to updates. They can be grouped into four major groups, namely, region encoding, prefix-based, multiplicative and hybrid. In this paper, we review on some existing labeling scheme based on each grouping. Through the review, we observed that each labeling scheme assign the node based on their unique identifier, thus, has its strengths and weaknesses. Finally, we provide some discussions based on the labeling grouping